Combination of DNA Vaccine and Immune Checkpoint Blockades Improves the Immune Response in an Orthotopic Unresectable Glioblastoma Model - Mathilde Bausart; Kevin Vanvarenberg; Bernard Ucakar; Alessandra Lopes; Gaëlle Vandermeulen; Alessio Malfanti; Véronique Préat (MDPI AG, 2022)
Combination immunotherapy has emerged as a promising strategy to increase the immune response in glioblastoma (GBM) and overcome the complex immunosuppression occurring in its microenvironment. In this study, we hypothesized that combining DNA vaccines-to stimulate a specific immune response-and dual immune checkpoint blockade (ICB)-to decrease the immunosuppression exerted on T cells-will improve the immune response and the survival in an orthotopic unresectable GL261 model. We first highlighted the influence of the insertion position of a GBM epitope sequence in a plasmid DNA vaccine encoding a vesicular stomatitis virus glycoprotein (VSV-G) (here referred to as pTOP) in the generation of a specific and significant IFN-γ response against the GBM antigen TRP2 by inserting a CD8 epitope sequence in specific permissive sites. Then, we combined the pTOP vaccine with anti-PD-1 and anti-CTLA-4 ICBs. Immune cell analysis revealed an increase in effector T cell to Treg ratios in the spleens and an increase in infiltrated IFN-γ-secreting CD8 T cell frequency in the brains following combination therapy. Even if the survival was not significantly different between dual ICB and combination therapy, we offer a new immunotherapeutic perspective by improving the immune landscape in an orthotopic unresectable GBM model.